Drawing and the Invisible (diségno, 2019)
In recent years, the Italian word disegno has expanded its range of meaning, embracing the influences of the English term design and thus involving the whole semantic field related to project conception and to the definition of spatial, sound and even behavioral configurations. This shift dialogues spontaneously with the attitude that has accompanied Studio Azzurro since its foundation, even though, precisely for this fact, it may prove potentially insidious. (read more)